Short on Time: Intertemporal Tensions in Business Sustainability - Slawinski, Natalie; Bansal, Pratima (Organization Science, 2015)
This inductive study of five firms in Alberta’s oil sands examines how organizations attend to the intertemporal tensions between the short term and long term that are inherent in business sustainability. Grounding our insights in organizational responses to the climate change issue, we find that firms that juxtapose the short term and long term also confront the tension between business and society. These firms are, therefore, more likely to recognize the complexity of climate change and the need for integrated, multidimensional solutions. These insights contribute to prior research in business sustainability.